Impact of chronic kidney disease stage on morbidity after gastrectomy for gastric cancer. Issue 4 (12th February 2021) - Suzuki, Satoshi; Kanaji, Shingo; Urakawa, Naoki; Takiguchi, Gosuke; Hasegawa, Hiroshi; Yamashita, Kimihiro; Matsuda, Takeru; Oshikiri, Taro; Nakamura, Tetsu; Kakeji, Yoshihiro
Abstract: Aim: The outcomes of gastrectomy for gastric cancer in patients at each severity of chronic kidney disease (CKD) remain unknown. Methods: We retrospectively analyzed the outcomes of 560 patients who underwent distal or total gastrectomy for gastric cancer between 2009 and 2018. We classified the patients into four groups based on estimated glomerular filtration rate: stage 1/2 (normal to mild, n = 375), stage 3a (mild to moderate, n = 122), stage 3b (moderate to severe, n = 43), and stage 4/5 (severe to end‐stage, n = 20) CKD. The relationship between CKD stage and the incidence of postoperative morbidity was analyzed. Results: CKD was a predictor of overall morbidity independent of age, gender, American Society of Anesthesiologists Performance Status, pulmonary comorbidity, extent of lymphadenectomy, and operation time in a multivariate analysis. The incidences of overall and severe morbidity were significantly increased with CKD progression (both P < .001). Compared to stage 1/2 CKD, the odds of overall morbidity were significantly elevated in stage 3a (odds ratio [OR] 1.87, P = .007), stage 3b (OR 3.86, P < .001), and stage 4/5 (OR 8.60, P < .001). The risk of procedure‐related morbidity was strikingly increased in stage 3b (OR 2.93, P = .004). The risk of procedure‐unrelated morbidity elevated markedly in stage 3a (OR 2.77, P = .001). A significant graded association between CKD progression and overall morbidity was also revealed in elderly patients ( P = .001). Conclusions: The severity of CKD predicts the likelihood and type of morbidity after gastrectomy and can guide surgical decision‐making for patients with gastric cancer. Abstract : Chronic kidney disease (CKD) progression increases the risk of morbidity following gastrectomy in gastric cancer patients. The risk elevates substantially at moderate CKD with an eGFR ≤ 45 ml/min/1.73 m 2 .